Evaluasi Kesesuaian Lahan Pada Rencana Satuan Kawasan Pengembangan (Rskp) A Pemukiman Transmigrasi Kecamatan Sangir Batanghari Kabupaten Solok Selatan - Edwin; Aulia Oktavia (Jurnal Riset Perkebunan, 2020)
Development Area Unit A is one of the transmigration development areas which will be developed in South Solok Regency. To see the potential of agricultural land in this area, it is necessary to evaluate the suitability of the land. This study uses a survey method. Determination of sample points using purposive sampling method. The land suitability analysis used the matching method with the help of the SPKL V.2 application. 1. In Land Unit 1 (SL) which covers 18,378 ha, a very suitable commodity (S1) to be developed is Candlenut for a plantation commodity. Meanwhile, oil palm and rubber commodities that are widely planted by the community at this time are only quite suitable (S2) in land units 1, 2, 3, 5, 6 and 7.Food commodities that can be developed in all land units are cassava, sweet potato and taro. at the marginally appropriate level (S3). Vegetable commodities that can be developed are spinach and eggplant at a marginal level (S3) in all land units except land units 4 and 8. Fruit commodities that can be developed are bananas, papaya, avocado, rambutan, guava, durian, star fruit. , melon, duku, cempedak, soursop, sugar apple, salak, sapodilla, longan and pineapple.